Implementation of Resonant and Passive Lossless Snubber Circuits for DC-DC Boost Converter - Kasiran, A.N.; Ponniran, A.; Bakar, A. A.; Yatim, M.H.; Noor, M. K. R.; Jumadril, J.N. (International Journal of Engineering and Technology, 2018)
This paper presents the comparison of resonant and passive lossless snubber circuits implementation for DC-DC boost converter to achieve soft-switching condition. By applying high switching frequency, the volume reduction of passive component can be achieved. However, the required of high switching frequency cause the switching loss during turn-ON and turn-OFF condition. In order to reduce the switching loss, soft-switching technique is required in order to reduce or eliminate the losses at switching devices. There are various of soft-switching techniques can be considered, either to reduce the switching loss during turn-ON only, or turn-OFF only, or both. This paper discusses comparative analyses of resonant and passive lossless snubber circuits which applied in the DC-DC boost converter structure. Based on the simulation results, the switching loss is approximately eliminated by applying soft-switching technique compared to the hard-switching technique implementation. The results show that the efficiency of resonant circuit and passive lossless snubber circuit are 82.99% and 99.24%, respectively. Therefore, by applying passive lossless snubber circuit in the DC-DC boost converter, the efficiency of the converter is greatly increased. Due to the existing of an additional capacitor in soft-switching circuit, it realizes lossless operation of DC-DC boost converter.